The Impact of Total Bank Assets, Income Diversification, and Financial Inclusion on the Stability of Islamic Commercial Banks in (Asian Journal of Social Science Studies, 2022)
For the five-year period 2014-2019, to determine and empirically demonstrate the influence of total bank assets on the stability of Islamic commercial banks in Indonesia, with the moderating variable of capital buffer. Sample size was determined using a purposive sampling approach, which included eight Islamic Commercial Banks. Using Moderated Regression Analysis to test hypotheses (MRA). As a result of these findings, it can be concluded that Islamic commercial banks in Indonesia are more stable if they have more diverse sources of income and greater financial inclusion. Islamic commercial banks in Indonesia's capital buffer can moderate the impact of income diversification on stability with the type of moderation generated by pure moderator, which indicates that stability can be improved. This is despite the fact that Islamic Commercial Banks' capital buffers are unable to counteract the negative effects of total assets and financial inclusion on their stability.